Pengaruh Motivasi Hedonis, Browsing dan Gaya Hidup Berbelanja Terhadap Pembelian Impulsif Di Online Shop (Studi Pada Mahasiswa Universitas Majalengka) (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2020)
This study aims to determine how the influence of Hedonic Motivation, Browsing andShopping Lifestyle on Impulsive Purchases at the Online Shop of Majalengka Universitystudents, either partially or simultaneously.The research method used is a survey method with descriptive and verification approaches.The sample used in this study were 100 respondents, the test instruments used in this studywere validity and reliability tests. The data analysis used in this research is classicalassumptions, multiple regression analysis, coefficient of determination, and hypothesistesting. For the partial test using the t test and test simultaneously using the F test.The results showed that hedonic motivation was in the high category, high category browsing,high shopping lifestyle, and high category impulsive buying. Partially hedonic motivation hasa positive and significant effect on impulsive buying, browsing has a positive and significanteffect on impulsive buying, and the shopping lifestyle has a positive and significant effect onimpulsive buying. Simultaneously, hedonic motivation, browsing and shopping lifestyle have apositive and significant effect on impulsive buying. This means that the higher the level ofhedonic motivation, browsing and shopping lifestyle, the higher the level of consumer impulsepurchases at the online shop